PEMBERIAN REWARD DAN PUNISHMENT TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA KELAS V - Safari, Riska Ardilla; Pratiwi, Ika Ari; Masfuah, Siti (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2023)
The learning method is used as a means used to achieve learning objectives, namely the teacher uses the reward and punishment method in learning Pancasila Education. This study used a descriptive qualitative research method conducted at SD Negeri 02 Tempur. This study aims to describe the impact of reward and punishment on learning outcomes in Pancasila Education. The data collection technique used was through the observation, interview and documentation stages consisting of 10 people including 1 class V teacher and 9 class V students consisting of 3 male students and 6 female students. The results of the study show that reward and punishment have an impact on students' affective learning outcomes. The positive impact of reward and punishment is that it makes students more accomplished and more confident in increasing their knowledge, students do not repeat their behavior or mistakes and have an attitude of responsibility. The negative impact of reward and punishment is that it makes students feel arrogant about their learning outcomes and makes students less confident.